Corruption Typology in Direct Regional Head Election - Aminah, Sitti (International Journal of Psychosocial Rehabilitation, 2020)
High cost politic in the direct regional head election (Pilkada) is one of the factors causing regional official corruption. The study aims to describe corruption during Pilkada and the lessons learned to improve future Pilkada. This study was used qualitative methods. The data collected through focus group discussions, literature studies and legislation analysis. The results of study shows that the typology of corruption involving interaction between actors during pilkada, including: (1) interaction between political leaders and regional bureaucrats; (2) interaction between regional government head as incumbents and political party elites; (3) interaction between regional government head candidates and the legislature and (4) interaction between regional government head candidates and informal leaders. Lessons learned are the need to strengthen political parties such us recruitment and regeneration of leaders; optimization of the functions and roles of electoral institutions, such as regional election commission (KPUD) and regional election supervisory agency (Bawaslu); political education for the community, increased election budget control, and effectiveness of the security budget. The study recommendations cover aspects of reforming legislation, reforming institutions and improving the political culture of the community.